2016
DOI: 10.1080/14766086.2015.1122546
|View full text |Cite
|
Sign up to set email alerts
|

Self-leadership, spirituality, and entrepreneur performance: a conceptual model

Abstract: This article investigates the value of integrating the constructs of self-leadership and spirituality as a resource for entrepreneurs to handle entrepreneurial demands/stressors. Entrepreneurship requires individuals to use their personal resources as they develop their business ventures. Entrepreneurs face multiple challenges as they start and grow their endeavors. We propose a conceptual model showing how the constructs of spirituality and self-leadership influence each other and have an impact on the thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 71 publications
1
29
0
4
Order By: Relevance
“…Seventh, this study found that entrepreneurial attitude mediates entrepreneurial education and students' mindset. This finding broadly supports the work of other studies by Godwin et al. (2016) ; Neck and Greene (2011) ; Opoku-antwi (2012) ; Denanyoh et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Seventh, this study found that entrepreneurial attitude mediates entrepreneurial education and students' mindset. This finding broadly supports the work of other studies by Godwin et al. (2016) ; Neck and Greene (2011) ; Opoku-antwi (2012) ; Denanyoh et al.…”
Section: Discussionsupporting
confidence: 93%
“…(2014) ; Mahendra et al. (2017) ; Godwin et al. (2016) ; Neck and Greene (2011) ; Opoku-antwi (2012) ; Denanyoh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Einolf (2013) found that daily spiritual experiences promote helping behaviors and a sense of others' needs. Godwin, Neck, and D'Intino (2016) propose that spiritual entrepreneurs perceive external business stressors as challenges rather than obstacles. Utilitarian theory suggests socially motivated persons are risk takers who intend to help others by breaking rules in specific conditions (Athanassoulis & Ross, 2010).…”
Section: Workplace Spirituality and Prosocial Rule-breakingmentioning
confidence: 99%
“…Duchon and Plowman (2005) found that a greater percentage of employees are on a spiritual journey exploring meaning and purpose in their lives during routine job duties (Duchon & Plowman, 2005). We argue that employees' WPS shapes their moral conviction, i.e., their primary values and perceived worldview, about activities, e.g., ethics, morality, helping attitudes, honesty, etc., they experience in the organization's daily life (Godwin et al, 2016).…”
Section: Workplace Spirituality and Moral Convictionmentioning
confidence: 99%
“…However, little is known about the extent to which these spiritual practices transform human potential. In this special issue, Godwin et al (2016) offer insights into the link between self-leadership and spirituality. A second area for future research relates to meaning and purpose.…”
Section: Future Research (Authored By Kathryn Pavlovich)mentioning
confidence: 99%